Evaluation of the impact of hydrogen‐rich water on the deaccumulation of heavy metals in butter. Issue 6 (2nd September 2022) - Alwazeer, Duried; Ceylan, Mehmet Murat; Bulut, Menekşe; Koyuncu, Mubin
Abstract: The transfer of heavy metals to products during food processing forms serious health concerns. The impact of cultured‐cream butter washing with hydrogen‐rich water (HRW) on the deaccumulation of arsenic (As), cadmium (Cd), antimony (Sb), mercury (Hg), and lead (Pb) in butter was evaluated. Raw cultured‐cream butter was washed with ordinary water or HRW prepared with molecular hydrogen (H2 ) and magnesium (Mg). While ordinary water‐washed butter samples exhibited an increase in As (7%), Cd (62%), and Pb (206%) and a decrease in Sb (26%) and Hg (17%) levels, HRW samples showed a decrease in As, Cd, Sb, and Hg levels ranged between 14 and 74% except for Pb that increased by only 29% (Mg) and 3% (H2 ). The proposed method is a green and eco‐friendly strategy to solve the transfer problem of heavy metals to food products. Abstract :